Obsession To Solve The Mystery Reflected In Martin Scorsese's Hugo Cabret Movie (2012): A Psychoanalytic Approach - Purnami, Dewi Indah; , Dr. Phil Dewi Candraningrum, S.Pd, M.Ed; , Titis Setyabudi, S.S,M.Hum (2013)
The research is proposed to analyze the obsession to solve the mystery reflected in Hugo Cabret movie 2012 by Psychoanalytic Approach. There are two objectives: the first is to analyze the movie based on its structural elements and technical elements, and the second is to analyze the main character's personality using a psychoanalytic approach. This study is a qualitative study, using Martin Scorsese's Hugo Cabret movie 2012 as of structural elements, and the secondary data. The primary data source is Hugo Cabret movie which is directed by Martin Scorsese, and the secondary data are some articles, book of literary and internet related to the subject. The method of collecting data in this research is library research by watching the movie, reading some related books and articles, accessing internet, taking notes of important part, arranging, and drawing conclusion the data. In analyzing the data, the writer employs descriptive analysis. The outcome of the study shows that the movie is illustrates how to reach obsession and solve the mystery. Finally, withe the spirit, hard work, and never gives up Hugo Cabret get the fact of a hidden message mystery by Hugo's father automaton.